Genetic Variability, Correlation and Path Analysis Study on Snap Melon (Cucumis melo L. var. momordica) Farmer’s Varieties - S. G, Pasha; Marker, S.; G., Sarath Chandra (International Journal of Bio-resource and Stress Management, 2020)
The present investigation was carried out to assess the genetic variability, correlation and path analysis for yield and its component traits in 15 Snap melon farmer’s varieties of Eastern Uttar Pradesh for 17 quantitative characters during Kharif- 2018. Analysis of variance showed significance differences for all the quantitative traits at 1% and 5% level of significance. Indicating considerable amount of genetic variation in different farmer’s varieties of Eastern Uttar Pradesh. The low difference between GCV and PCV depicted that a little or no influence of environment on the expression of the various quantitative traits. High heritability coupled with high genetic advance was depicted by for fruit weight at average followed by number of seeds fruit-1 and 100 seed weight, indicating a predominance of additive gene effects and the possibilities of effective selection based on these traits for snap melon improvement. Therefore, these traits may be used as selection indices for genetic improvement of Snap melon farmer’s varieties. Node at first female flower appearance followed by number of fruits plant-1, fruit length, fruit diameter, fruit flesh thickness and fruit weigh at average show positive significant correlation and direct effect on yield plant-1 further proves their genetic worth for selection breeding through pure line/ pedigree method.